2009
DOI: 10.1080/01635580802567158
|View full text |Cite
|
Sign up to set email alerts
|

Selective Induction of Apoptosis of Human Oral Cancer Cell Lines by Avocado Extracts Via a ROS-Mediated Mechanism

Abstract: Avocados have a high content of phytochemicals with potential chemopreventive activity. Previously we reported that phytochemicals extracted from avocado meat into a chloroform partition (D003) selectively induced apoptosis in cancer but not normal, human oral epithelial cell lines. In the present study, we observed that treatment of human oral cancer cell lines containing high levels of reactive oxygen (ROS) with D003 increased ROS levels twofold to threefold and induced apoptosis. In contrast, ROS levels inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
64
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 44 publications
6
64
1
1
Order By: Relevance
“…Consequently, understanding the intracellular molecular mechanisms involved in avocado-induced apoptosis may lead to specific targeted therapeutic interventions (Brooke et al, 2011). Since constituents isolated from the avocado (e.g., chloroform-soluble extract D003) have been shown to induce apoptosis via a reactive oxygen speciesmediated mechanism (Ding et al, 2009) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, understanding the intracellular molecular mechanisms involved in avocado-induced apoptosis may lead to specific targeted therapeutic interventions (Brooke et al, 2011). Since constituents isolated from the avocado (e.g., chloroform-soluble extract D003) have been shown to induce apoptosis via a reactive oxygen speciesmediated mechanism (Ding et al, 2009) …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Persea americana Mill var. Hass (Lauraceae) has been shown to inhibit growth and/or to induce apoptosis in prostate and oral epithelial cancer cell lines (D'Ambrosio et al, 2011;Ding et al, 2009). Despite this information, no data are available to establish whether P. americana var.…”
Section: Introductionmentioning
confidence: 99%
“…Avocado is a food rich in unsaturated fatty acids (Dreher & Davenport, 2013) tocopherols, phytosterols, phenolic compounds, and procyanidins (Wang et al, 2010); and it has been demonstrated that its consumption diminishes cancer incidence (Ding et al, 2007;Ding et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Increased ROS and Ca 2+ production along with other factors played important role in inducing apoptosis in tsgh8301 human bladder cancer cells. Several natural products targets cancer cells by elevating ROS levels (Ding et al 2009;Jeong et al 2010;Widodo et al 2010). Hex-LI and CHCl 3 -LI significantly increased production of ROS in HeLa cells as compared to their respective controls.…”
Section: Discussionmentioning
confidence: 98%